The Study of Marketing Mix on Cultural Tourism within the Vicinity Central Provincial Cluster - Kwamkhunkoei, Jessada; Na Thalang, Chawalee (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
The purposes of this research were to: 1) Study the behavior of Thai Tourists within cultural tourism in the Vicinity Central Provincial Cluster; 2) Study Thai tourists and their opinions on the importance of marketing mix within cultural tourism in the Vicinity Central Provincial Cluster; 3) Study the Relationships between Personal Characteristics of Thai Tourists and the behavior within Cultural Tourism in the Vicinity Central Provincial Cluster. And 4) compare opinions on the significant effects of marketing mix according to personal characteristics and preferences of Thai tourists. This research is quantitative research. The group studied were Thai tourists who traveled to the Vicinity Central Provincial Cluster. The Methodology used to collect information comes from questionnaires of 400 tourists. The data statistics were analyzed for frequency distribution, percentage, mean, and standard deviation. Therefore, a hypothesis was formed by using the Chi-Square test, t-test, One-way ANOVA, and Least Significant Difference Test (LSD). The results showed that: 1) Thai tourists traveling for cultural tourism travel with the intention of rest and relaxation. The majority travel with families and relatives during Saturday - Sunday. Their total trip average expenses are less than 2,000 baht. Most Thai tourists travel in groups of 2-3 people and make a trip in less than 3 months/time. 2) Thai tourists’ opinions on marketing mix within cultural tourism in the Vicinity Central Provincial Cluster showed a high level 3) The Relationship between personal Characteristics of Thai tourists and Behavior within Culture tourism in the Vicinity Central Provincial Cluster has to relationship the mode of travel. and 4) In general, the different personal characteristics and preferences of Thai tourists did not influence a significant difference in opinion on the level of importance of marketing mix about cultural tourism in the Vicinity Central Provincial Cluster.